KONSEP KESEHATAN MENTAL DALAM PENDIDIKAN ISLAM Analisis Pemikiran Prof. Zakiah Daradjat - Uswatun; Aulia (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
Abstract: This study aims to determine and describe the concept of mental health according to Zakiyah Daradjat through Islamic education. This study uses a descriptive qualitative research method with a library research approach, namely a study conducted by searching for and discussing related literature or books. The data sources used are Zakiyah Daradjat's books as primary data sources and other books related to the research object as secondary data sources. The results of this study indicate that the concept of Islamic education in mental health according to Zakiah Daradjat is a change in attitude and behavior in accordance with the instructions of Islamic teachings, aimed at improving mental attitudes that are manifested in actions, both for the needs of oneself (individual) and others (society). Islamic education plays a role in controlling these morals and personalities. With Islamic guidance, students are helped to improve their personalities starting from the basic aspects, namely their mental condition. The concept is divided into two, namely: (1) theoretically (2) practically. Both theories include: (a) recognition, understanding, and urgency of individual mental health (b) ways of guidance that are carried out in real educational environments (family, school, community) by paying attention to the psychological development of students (c) instructions for handling mental health problems, namely by worshiping and getting closer to Allah Ta'ala.